Synthesis of fused heterocyclic aromatic compounds as potential antiplasmodial agents - Jacobs, Leon (Stellenbosch : Stellenbosch University, 2017)
Stellenbosch University. Faculty of Science. Dept. of Chemistry and Polymer Science.